Visionary-Adaptive Islamic Educational Leadership in Strengthening Madrasah Quality - Zul Fitrotul Hanifiyah; Siti Aisah; Ahmad Halid; Sarifatul Jannah (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2026)
Academic supervision at MA Darul Istiqomah Al Haya identified adequate subject-matter mastery but persistent reliance on lecturing. This study examines two connected questions: how the madrasah head translated an instructional-quality vision into supervision follow-up and teacher development, and how improvement strategies were adapted to teacher readiness, institutional resources, technology access, and pesantren characteristics. An embedded mixed-methods single-case design with qualitative priority was conducted from April 6 to 26, 2026. The quantitative strand involved all five teachers and 28 students; qualitative participants comprised the madrasah head, five teachers, one education staff member, and three students. Data were generated through questionnaires, semi-structured interviews, classroom observations, and document analysis, then integrated through side-by-side comparison. The first finding shows that supervision evidence was converted into a shared improvement direction, evaluation meetings, scheduled coaching, and differentiated assistance. Four of five teachers reported that this support helped them vary methods and media. The second finding shows context-sensitive adaptation: teachers combined projector-mediated videos and quizzes with discussion, concrete media, group work, worksheets, and environmental observation while respecting restrictions on personal devices. Twenty-two of 28 students reported more varied and participatory lessons. The study concludes that visionary direction, adaptive mobilization, and Islamic ethical values function as one supervision-to-learning mechanism. Institutionalized supervision cycles, collective reflection, and accessible documentation are recommended to sustain teacher professional learning.